2010
DOI: 10.14254/2071-789x.2010/3-1/9
|View full text |Cite
|
Sign up to set email alerts
|

Functionality of Product Packaging: Surveying Consumers’ Attitude Towards Selected Cosmetic Brands

Abstract: ABSTRACT. The paper reviews the functions of product packaging and applies the theoretical findings to the empirical research, focusing on secondary and primary data of packaging of cosmetic products. A survey was performed in Kaunas City, Lithuania, to determine the consumers' opinion on four selected cosmetic brands: two brands from Lithuania and two of foreign origin, namely a) Optima Linija and BIOK; b) The Body Shop and L'Occitane. The chosen cosmetic brands are presented as separate mini case studies wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 3 publications
0
21
0
3
Order By: Relevance
“…Packaging design becomes more significant when it is designed for aesthetics and to deliver specific information to consumers. Grundey [2010] confirmed that packaging plays an important role in the process of creating a product, promoting it and finally selling it. All functions of the packaging as protection, utility and communication are important, and have to be analyzed when creating a new product.…”
Section: Functions Of the Packaging Of Dermocosmetic Productsmentioning
confidence: 79%
“…Packaging design becomes more significant when it is designed for aesthetics and to deliver specific information to consumers. Grundey [2010] confirmed that packaging plays an important role in the process of creating a product, promoting it and finally selling it. All functions of the packaging as protection, utility and communication are important, and have to be analyzed when creating a new product.…”
Section: Functions Of the Packaging Of Dermocosmetic Productsmentioning
confidence: 79%
“…Typically, taste offers satisfaction (Drichoutis et al, 2006), and sweetness is associated with hedonic responses (Yoon Kin Tong et al, 2012). So that product packaging has emotional value for consumers (Grundey, 2010), which can provide a sense of pleasure and benefit from attractive packaging (Underwood, 2003). From the results of the review of previous research, the next hypothesis can be proposed, that: H-2: Product attributes have a positive significant effect on hedonic value.…”
Section: Effect Of Product Attributes On Hedonic Valuementioning
confidence: 99%
“…Di lapangan, proses pembuatan kemasan sering ditemukan masalah pada mesin soontrue. Seperti bandrol atau laminasi [1] belakang kemasan [1] tidak senter atau sering reject pada kemasan, untuk itu perlu dirancang mesin baru. Hasil perancangan diharapkan dapat menjadi solusi untuk melakukan perbaikan yaitu hasil produksi yang lebih banyak dan posisi bandrol atau label presisi.…”
Section: Pendahuluanunclassified